Authority Fragmentation in the Digital Age: A ‎Social Network Analysis of Islamic Scholars and ‎Influencers' Networks in Indonesia - Izza Amalia; Jacqueline Geofrey Makolo; Oman Sukmana; Tri Sulistyaningsih; Tonny Dian Efendi; Moulita Moulita; Asnath Naftali Remtulla (JPI: Jurnal Pustaka Indonesia, 2026)
The rise of digital media has fundamentally reconfigured the landscape of Islamic religious authority in Indonesia, enabling a proliferating class of social media influencers to operate alongside and often in competition with traditionally trained ulama. This study maps the structural dynamics of authority networks among Islamic scholars and digital influencers on Instagram and YouTube using Social Network Analysis (SNA). Data were collected from 52 Indonesian-language Islamic accounts (minimum 100,000 followers) active in 2020–2024, coded into a relational matrix of 134 edges. Network visualization and centrality analysis were conducted in Gephi 0.10.1, applying degree centrality, betweenness centrality, closeness centrality, and bridging coefficient measures alongside Louvain modularity-based community detection. Results reveal four structurally distinct communities: Traditional Scholarship, Popular Dakwah, Progressive-Critical Islam, and Islamism/Political Islam. Traditional scholars dominate degree centrality (mean degree = 8.3) but record the lowest bridging coefficients (mean = 0.18), indicating structural insularity. Digital influencers exhibit the highest bridging coefficients (mean = 0.71), confirming their role as inter-community bridges, while Progressive-Critical Islam appears completely isolated (zero cross-community edges). These findings confirm that digital media accelerates authority fragmentation rather than unifying it, producing structurally disconnected clusters with significant implications for Islamic normative contestation and social cohesion in Indonesia. This study contributes novel insights by (1) empirically demonstrating authority fragmentation through a network-based analytical framework, (2) integrating classical sociological theories of authority with computational Social Network Analysis in the context of digital religion, and (3) revealing the structural brokerage role of digital influencers as key intermediaries in shaping contemporary Islamic discourse.